2008
DOI: 10.1631/jzus.b0710546
|View full text |Cite
|
Sign up to set email alerts
|

Values of endoscopic ultrasonography for diagnosis and treatment of duodenal protruding lesions

Abstract: Abstract:Objective: The diagnoses of patients with duodenal protruding lesions are difficult when using conventional examinations such as computed tomography (CT) and conventional endoscope etc. Thus, we investigated the clinical value of endoscopic ultrasonography (EUS) with miniature ultrasonic probes on the diagnosis and treatment of duodenal protruding lesions. Methods: Patients with duodenal protruding lesions who were indicated for EUS were examined by EUS with 12~15 MHz miniature ultrasonic probes and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…So EUS can provide more diagnostic information about submucosal lesions, which will help to diagnose and differentiate submucosal lesions. At the present, EUS is the best means to diagnose submucosal tumors (Chen et al, 2001;Gress et al, 2001;Fusaroli and Caletti, 2005;Xu et al, 2008). Ultrasonic image of the present case showed a hypoechoic lesion, internal echos of which were uneven, with many lumen-like structures.…”
Section: Discussionmentioning
confidence: 61%
“…So EUS can provide more diagnostic information about submucosal lesions, which will help to diagnose and differentiate submucosal lesions. At the present, EUS is the best means to diagnose submucosal tumors (Chen et al, 2001;Gress et al, 2001;Fusaroli and Caletti, 2005;Xu et al, 2008). Ultrasonic image of the present case showed a hypoechoic lesion, internal echos of which were uneven, with many lumen-like structures.…”
Section: Discussionmentioning
confidence: 61%
“…Because BGH was usually covered with normal mucosa, the value of pinch biopsies might be limited. Endoscopic ultrasound (EUS) may be helpful in the diagnosis and treatment of BGH [12]. In our case, taking into account that a complete specimen for histological examination could be obtained easily by HSP, we did not perform a EUS.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic lipomas are rare tumours. In 2008, Xu et al 6 reviewed 169 cases of protruding lesions in the duodenum and found only one lipoma (0.59%). In 2006, Hois et al 7 analyzed 6000 CT scans and identified pancreatic lipomas in 5 of them (0.083%).…”
Section: Discussionmentioning
confidence: 99%